Role of endothelial dysfunction in cardiovascular disease: A review - Kadirvelu, Amudha; Tan, Kim Heung; Choy, Anna Maria; Mustafa, Mohd Rais (Faculty of Medicine, University of Malaya, 2000)
Cardiovascular disease remains to be the chief Cluse of death in industrialized countries. Although me cause of cardiovascular disease remain unknown. it is now clear that an impairment of tissue perfusion represents the primary problem. Three main factors contribute to the impairment of tissue perfusion, which are: enhanced vasoconstrictor responses, increased interaction of circulating blood cells and structural changes of the arterial intima. Endothelium, due to its strategic anatomical location between the circulating blood and vascular smooth muscle is a primary target and mediator of cardiovascular disease. The importance of endothelium in modulating the activity of vascular smooth muscle and therefore in regulating vascular tone was first recognized by the pioneering studies of Furchgott and Zawadzki (I). Functional integrity of the endothelium is crucial for the maintenance of blood flow and antithrombotic capacity beause endothelium releases humoral factors that control muscle relaxation and contraction, thrombogenesis and fibrinolysis and platelet activation and inhibition.